Carbon ion radiotherapy performed as re-irradiation using active beam delivery in patients with tumors of the brain, skull base and sacral region - Combs, Stephanie; Heiland, Adriana Michaela; Nikoghosyan, Anna; Ackermann, Benjamin; Jäkel, Oliver; Haberer, Thomas; Debus, Jürgen (Radiotherapy and oncology, 2011)
Introduction - To asses carbon ion radiation therapy (RT) performed as re-irradiation in 28 patients with recurrent tumors. - Materials and methods - Twenty-eight patients were treated with carbon ion RT as re-irradiation for recurrent chordoma and chondrosarcoma of the skull base (n=16 and n=2), one chordoma and one chondrosarcoma of the os sacrum, high-risk meningioma (n=3), adenoid-cystic carcinoma (n=4) as well as one SCCHN. All patients were treated using active raster scanning, and treatment planning was performed on CT- and MRI-basis. All patients were followed prospectively during follow-up. - Results - In all patients re-irradiation could be applied safely without interruptions. For skull base tumors, local tumor control after re-irradiation was 92% at 24months and 64% at 36months. Survival after re-irradiation was 86% at 24months, and 43% at 60months. In all three meningiomas treated with C12 for re-irradiation, the tumor recurrence was located within the former RT-field. Two patients developed tumor progression at 6months, and in one patient the tumor remained stable for 67months. In patients with head-and-neck tumors, three patients developed local tumor progression at 12, 24 and 29months after re-irradiation. Median local progression-free survival was 24months. For sacral tumors, re-irradiation offered palliation with tumor control for 24 and 36months. - Conclusion - Due to the physical characteristics particle therapy offers a new treatment modality in cases with tumor recurrences. With carbon ions, the additional biological benefits may be exploited for long-term tumor control. Further evaluation in a larger patients’ cohort will be performed in the future.
Available online 25 November 2010
Gesehen am 08.04.2022